In‐Sensor Computing‐Based Smart Sensing Architecture Implemented Using a Dual‐Gate Metal‐Oxide Thin‐Film Transistor Technology - Tengteng Lei; Yushen Hu; Xinying Xie; Runxiao Shi; Man Wong (Advanced Electronic Materials)
Abstract An array of sensors generating a collection of correlated signals can benefit from integration with a “smart” system for autonomous inferencing. Mimicking their biological counterparts, smart sensor systems shall possess the capabilities of sensing, memory, and neuromorphic computation. However, state‐of‐the‐art biomimetic systems either do not employ a full set of devices to cover the complete range of capabilities or incorporate devices that are capable of all but appropriate only for a limited range of sensing applications. Presently proposed is a smart sensor architecture that combines an array of sensing elements with an overlapping array of computing and memory elements, thus emulating an innervated peripheral sensing system (IPSS) capable of local and autonomous neuromorphic in‐sensor data pre‐processing. Compatibility of the proposed architecture with functionally distinct elements for sensing, memory, and computing removes the restrictive demand for a single element simultaneously capable of all, thus making this architecture more generally applicable to a wider range of sensors and usage scenarios. An artificial synapse as a computing element is implemented using dual‐gate (DG) thin‐film transistors (TFTs) and the low‐leakage current of transistors based on metal‐oxide semiconductors allows the deployment of capacitors as memory elements. The outputs of the IPSS are passed on to an adjacent artificial neural network (ANN) for near‐sensor inferencing. Monolithic integration of the IPSS and the ANN is made possible by the deployment of the same memory and computing elements in their construction. A smart tactile sensing system based on the proposed architecture is constructed and characterized. The functionality of the system is demonstrated by its application to the classification of a set of tactile images of 3‐dimensionally printed alphabet stamps.